Is necessity the mother of disruption? - Stephanie Preißner; Christina Raasch; Tim Schweisfurth (Kiel Institute for the World Economy (IfW), 2017)
This study investigates the origins of disruptive innovation. According to the canonical model, disruptive innovations do not originate from existing customers - in contrast with what the user innovation literature would predict. We compiled a unique historical and content-analytic dataset based on 62 cases identified from the disruptive innovation literature. We found that 44% of the disruptive innovations in this sample were originally developed by users. Disruptive innovations are more likely to originate from users (producers) if the environment is characterized by high levels of turbulence in customer preferences (technology). Disruptive innovations involving high functional (technological) novelty, tend to be developed by users (producers). Users are also more likely to be the source of disruptive process innovations, and to innovate in weaker appropriability environments. Our paper is among the first to link the disruptive and user innovation literatures. We contribute to both and offer guidance to managers on the likely source of disruptive threats.
Keywords: D83; L17; M19; O31; O34; 330; user innovation; disruptive innovation; market orientation; radical innovation; environmental turbulence